An explanation of the underdevelopment of China’s service sector from the perspective of demand - Fan, Wenjing; Pan, Jiadong; Zhou, Minghai (Taylor & Francis, 2019)
The share of the service sector in China is significantly lower than that in most countries at the same level of income. Figures reveal that an insufficiency in both consumer and producer demand may be one of the reasons. We find that the demand insufficiency mainly stems from high consumer preferences for saving and China’s export-oriented trade structure. These excessive saving tendencies limit consumer demand for service products and thus hamper the development of consumer services in China. The rapid development of the processing trade also impedes the interrelation between the domestic manufacturing and service industries, reduces the effective demand for local producer services from the manufacturing industry, and ultimately restricts the growth of the producer service industry in China.